The Effects of Intrathecal Dexamethasone versus Fentanyl on Post-Spinal Shivering in Patients Undergoing Transurethral Prostatectomy - Ali Amer,; Ekram Rajhi, (AlQalam Journal of Medical and Applied Sciences, 2025)
Shivering is a common complication of spinal anesthesia (incidence 40-70%), particularly problematic during transurethral prostatectomy (TURP) due to perioperative hypothermia and elderly patients' comorbidities. This randomized controlled trial compared intrathecal dexamethasone (8mg) and fentanyl (20µg) as adjuvants to bupivacaine for preventing post-spinal shivering in 51 ASA I-II patients undergoing TURP. Patients were allocated to dexamethasone (Group D), fentanyl (Group F), or saline control (Group C). Shivering incidence was significantly lower in Group D (11.8%) and Group F (23.5%) versus Group C (52.9%) (p<0.05). Shivering severity (measured via Crossley scale) and meperidine rescue doses were significantly reduced in intervention groups. Core temperature decline was attenuated in Groups D/F versus C (p<0.05 at 15-45min). Sensory/motor block duration was prolonged in intervention groups without hemodynamic differences. Both dexamethasone and fentanyl effectively reduced shivering incidence and severity without significant adverse events, providing safe alternatives for TURP patients.